Penentuan Jaringan Jalan untuk Lajur Pesepeda (Studi Kasus: Kota Semarang) - Hafidz Aliyudin; Rukuh Setiadi (Teknik PWK (Perencanaan Wilayah Kota), 2021)
The increase in the population of Semarang City has implications for the rapid increase in the number of motorized vehicles. On that basis, Semarang City Government developed a policy idea with a road network development program for bike lanes as a solution to increase the use of non-motorized vehicles. The lack of supporting infrastructure for bicycle lanes makes the community feel less comfortable, less safe, and less interested when using bicycles on the highway. The purpose of this study is to determine the road network for bike lane in Semarang city. The method used is a mixed method with descriptive analysis and overlay analysis. The results of this study stated that the road network for bicycle lanes in Semarang City more suitable for recreation and sports, the road network zone for bicycle lane in Semarang City divided is five priorities, and the suitability of the road network zones for bicycle lanes and the bicycle road network plan shows there are 16 suitable road networks out of 19 planned road networks.